2015
DOI: 10.2196/jmir.4734
|View full text |Cite
|
Sign up to set email alerts
|

“Why Didn’t it Work?” Lessons From a Randomized Controlled Trial of a Web-based Personally Controlled Health Management System for Adults with Asthma

Abstract: BackgroundPersonally controlled health management systems (PCHMS), which may include a personal health record (PHR), health management tools, and information resources, have been advocated as a next-generation technology to improve health behaviors and outcomes. There have been successful trials of PCHMS in various health settings. However, there is mixed evidence for whether consumers will use these systems over the long term and whether they ultimately lead to improved health outcomes and behaviors.Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 40 publications
0
45
2
Order By: Relevance
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were undertaken in the United States (75%; n=12; [51-56, 59-61, 63-65]), followed by Australia (n=2; [57,62]), Canada (n=1; [50]) and New Zealand (n=1; [58]). Studies included a range of ages: children (44%; n=7; [51, 53, 59-61, 64, 65]), adolescents (13%; n=2; [54,55]), adults (38%; n=6; [50,52,57,58,62,63]) and mixed sample (6%; n=1; [56]). Between 35-82% of the samples were female.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations